A Retrospective Study: Incidence and Management of Genodermatoses - Dwi Ratna Adisty; Iskandar Zulkarnain (Faculty of Medicine, Universitas Airlangga, 2016)
Background: Genodermatoses are rare congenital diseases of the skin especially genetically determined. Genodermatoses can be grouped into three categories: chromosomal, single gene, and multifactorial. Skin condition in the genodermatoses patients not only important to start the right therapy but also to detect the other system diorders including malignancy. Objective: To evaluate the incidence of genodermatoses and to know the management of each patients. Methods: A retrospective study of genodermatoses patients in Kemuning Ward Dr. Soetomo Hospital Surabaya in 5 years period 2010-2014. Results: The incidence of genodermatoses among patients in Kemuning Ward was 10 of 1912 (0.52%).They are five males and five females (1:1). This study had shown that the diagnosis of genodermatoses were ichthyosis in 3 patients, epidermolysis bullosa (EB), and xeroderma pigmentosum (XP) each in 2 patients, neurofibromatosis (NF) type 1 in 1 patient, lymphangioma circumscriptum in 1 patient, and verrucous epidermal nevi in 1 patient. Positive family history of the same disease was obtained in one patients with xeroderma pigmentosum. No data of consanguinity found in ten patients. Conclusion: Small number of patients with genodermatoses due to the small incidence of the disease. The management vary depends on the clinical manifestations observed in each patient. Key words: genodermatoses, incidence, management, retrospective.